The The influence of customer engagement on brand loyalty: social interactivity and satisfaction as mediating variables - Ridwan Muhammad; Abror Abror (Marketing Management Studies, 2021)
The purpose of this research is to analyze how Customer Engagement affects Brand Loyalty on Maxim users in Padang City with Social Interactivity and Satisfaction as mediation variables. This research was conducted using quantitative method. The population of this study is all users who have used Maxim at least 1 time a week and used the Maxim app for the last 3 months. A sample of 290 respondents. This study used structural equation model (SEM) test with smart PLS 3.0 software as the data analysis tools. The results of this study found that: (1)Customer Engagement has a significant direct influence on Social Interactivity. (2) Customer Engagement has a significant direct influence on Satisfaction. (3) Social Interactivity has a significant direct influence on Satisfction. (4) Social Interactivity has a significant direct influence on Brand Loyalty. (5) Satisfaction has a significant direct influence on Brand Loyalty. (6) Customer Engagement has a significant direct influence on Brand Loyalty. (7) Customer Engagement has a significant indirect influence with Brand Loyalty with Social Interactivity as a mediation variable. (8) Customer Engagement has a significant indirect influence with Brand Loyalty with Satisfaction as a mediation variable.